SINERGI PENDIDIKAN NONFORMAL DAN KELUARGA DALAM MENANAMKAN PENDIDIKAN KARAKTER ANAK USIA DINI - Lodia Kubela; J.L. Kundre (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education for early childhood is crucial as it lays the foundation for moral and social development. However, modern environmental challenges and inconsistent value reinforcement often hinder optimal character formation. This study aims to explore the concept of early childhood character education, analyze the distinct roles of family and nonformal education, and emphasize the necessity of their synergy. Employing a qualitative literature review method, this paper synthesizes theoretical frameworks and empirical findings on early childhood development, character education strategies, and the complementary functions of family and nonformal institutions such as PAUD and community-based learning centers. The results indicate that character education cannot rely solely on one environment; it requires consistent alignment between familial upbringing and nonformal educational programs. When both parties collaborate through open communication, shared values, and active parental involvement, children experience continuous reinforcement of positive behaviors such as honesty, discipline, empathy, and responsibility. This synergy creates a holistic learning ecosystem that significantly enhances character internalization. Consequently, integrating family and nonformal education is essential to foster a generation with strong moral integrity, social adaptability, and readiness for future challenges.